A specific inhibitor of protein kinase CK2 delays gamma-H2Ax foci removal and reduces clonogenic survival of irradiated mammalian cells - Zwicker, Felix; Ebert, Maren; Huber, Peter E.; Debus, Jürgen; Weber, Klaus-Josef (Radiation oncology, 2011)
Background: The protein kinase CK2 sustains multiple pro-survival functions in cellular DNA damage response and its level is tightly regulated in normal cells but elevated in cancers. Because CK2 is thus considered as potential therapeutic target, DNA double-strand break (DSB) formation and rejoining, apoptosis induction and clonogenic survival was assessed in irradiated mammalian cells upon chemical inhibition of CK2. - Methods: MRC5 human fibroblasts and WIDR human colon carcinoma cells were incubated with highly specific CK2 inhibitor 4,5,6,7-tetrabromobenzotriazole (TBB), or mock-treated, 2 hours prior to irradiation. DSB was measured by pulsed-field electrophoresis (PFGE) as well as gamma-H2AX foci formation and removal. Apoptosis induction was tested by DAPI staining and sub-G1 flow cytometry, survival was quantified by clonogenic assay. - Results: TBB treatment did not affect initial DNA fragmention (PFGE; up to 80 Gy) or foci formation (1 Gy). While DNA fragment rejoining (PFGE) was not inhibited by the drug, TBB clearly delayed gamma-H2AX foci disappearence during postirradiation incubation. No apoptosis induction could be detected for up to 38 hours for both cell lines and exposure conditions (monotherapies or combination), but TBB treatment at this moderately toxic concentration of 20 μM (about 40% survival) enhanced radiation-induced cell killing in the clonogenic assay. - Conclusions: The data imply a role of CK2 in gamma-H2AX dephosporylation, most likely through its known ability to stimulate PP2A phosphatase, rather than DSB rejoining. The slight but definite clonogenic radiosensitization by TBB does apparently not result from interference with an apoptosis suppression function of CK2 in these cells but could reflect inhibitor-induced uncoupling of DNA damage response decay from break ligation.
Gesehen am 30.01.2023